Light Pollution, Urbanization and Ecology - Hufnagel, Levente (IntechOpen, 2022)
Light Pollution, Urbanization and Ecology presents a comprehensive review of light pollution, including scientific research on the ecological impacts of artificial illumination in urban regions. Chapters cover such topics as general ecological aspects, plants, invertebrate and vertebrate biology, and environmental and landscape architecture aspects of this interesting and important topic.